Coverage optimization algorithm and implementation based on computational graph for mobile communication network and IoT service - Haobin WANG; Wei HUANGFU; Yaxi LIU; Wei LIU (物联网学报)
The research on the mobile communication network optimization for the Internet of things large connection and differential service quality has great significance.Mobile communication network optimization is a multi-parameter complex optimization problem with high computational cost function.In order to provide the basis for parallelization of operations,the calculation method of the coverage quality assessment of the mobile communication network based on the computational graph was introduced.Based on the calculation graph,the derivative calculation method of the coverage quality index was obtained,by back propagation to guide the optimization of the antenna parameters.The momentum method was used to accelerate the convergence speed of the optimization algorithm.The simulation results show that the algorithm is suitable for the coverage optimization in mobile communication network.